12-month trajectory and predictors of affect balance in nursing home residents living with dementia. (14th July 2022) - Kolanowski, Ann; Zhu, Shijun; Van Haitsma, Kimberly; Resnick, Barbara; Boltz, Marie; Galik, Elizabeth; Behrens, Liza; Eshraghi, Karen; Ellis, Jeanette
Abstract: Objectives: Emotional expressions in late-stage dementia have traditionally been studied within a deficit paradigm. Moving the narrative of the dementia trajectory from a solely negative pathological experience to one that acknowledges the potential for positive experiences aligns with international recommendations for living well with dementia. The purpose of this study was to extend prior research by examining the pattern of well-being using affect balance, the ratio of positive to negative affect, in nursing home residents living with dementia over 12 months and its association to factors that could potentially influence resident well-being. Method: This study was a secondary analysis of baseline, 4 and 12-month data from a pragmatic clinical trial. A total of 536 residents with moderate to severe cognitive impairments from 55 nursing homes were included in the multivariable linear mixed model regression analyses. Results: Resident function, the number of registered nurse hours devoted to care in the facility, and the quality of staff interaction predicted higher affect balance over time after controlling for other variables. Conclusion: The findings provide support for the utility of affect balance as a meaningful outcome measure of well-being for persons living with dementia. In addition, results point to specific interventions (i.e. maintaining/improving resident function, providing adequate nurse staffing levels, and improving staff communications skills) that can serve as the focus for both research and practice to help residents live well with dementia. Clinicaltrials.gov (NCT03014570).